The meaning of soul : Black music and resilience since the 1960s - Lordi, Emily J., 1979- (Refiguring American music., 2020)
"THE MEANING OF SOUL discusses Black resilience and innovation through soul music and soul logic. Emily Lordi analyzes soul music and musicians from the 1960s, the 1970s, and after, bridging the different valences of soul as a way of moving through the world. The book encompasses soul's racial-political meanings while being sensitive to the details of the music and small details that shaped artists' lives and their relationship to soul. Chapter 1 is about the relationship of soul and jazz music, tracing soul's emergence in the late 1960s as a mode that underscored the redemptive possibilities of Black suffering. Lordi describes how soul music channeled the styles and techniques of the church into secular lyrical content, while soul discourse simultaneously drafted religious logic into a secular faith in collective redemption. Chapter 2 is about how soul artists transformed expressive deprivation into musical abundance by crafting innovative covers of other artists' songs. Landmark covers of this type propelled many soul artists, including Nina Simone and Aretha Franklin, into the spotlight, their displacement turned into stylized survivorship. In chapter 3, Lordi unpacks jazz improvisation and soul adlibs as performing a hard-won achievement of self-trust, trusting oneself enough to break with destructive or stifling conventions. Chapter 4 extends inquiry into the performative relationships with self and others discussed in the previous chapter, by exploring a deeper sense of interiority and a broader scope of sociality as enacted through falsetto vocals. Lordi talks about soul falsettos as used by Ann Peebles, Al Green, Isaac Hayes, and Minnie Riperton, and the ways falsetto signifies different things contextually. Lordi ends the book with a chapter on false endings - bringing the song to a close before striking it up again - symbolizing soul's message of Black group resilience, not a matter of stasis, but of change. The false ending signals the endurance necessary to keep changing, not only oneself, but one's surroundings. Through the close attention to vocal and musical details, as well as to singers beyond the familiar and mostly male stars, Lordi retells the much-told story of soul in a new and rich way. This book will be of interest to general readers and scholars in African American studies, American studies, Black diaspora studies, popular music, and critical theory"--